Apigenin induced apoptosis in esophageal carcinoma cells by destruction membrane structures. Issue 4 (5th October 2015) - Zhu, Haiyan; Jin, Hua; Pi, Jiang; Bai, Haihua; Yang, Fen; Wu, Chaomin; Jiang, Jinhuan; Cai, Jiye
Summary: Apigenin has shown to have killing effects on some kinds of solid tumor cells. However, the changes in cell membrane induced by apigenin on subcellular‐ or nanometer‐level were still unclear. In this work, human esophageal cancer cells (EC9706 and KYSE150 cells) were employed as cell model to detect the cytotoxicity of apigenin, including cell growth inhibition, apoptosis induction, membrane toxicity, etc. MTT assay showed that apigenin could remarkably inhibit the growth and proliferation in both types of cells. Annexin V/PI‐based flow cytometry analysis showed that the cytotoxic effects of apigenin in KYSE150 cells were mainly through early apoptosis induction, while in EC9706 cells, necrosis, and apoptosis were both involved in cell death. The morphological and ultrastructural properties induced by apigenin were investigated at single cellular‐ or nanometer‐level using atomic force microscopy (AFM). Additionally, lactate dehydrogenase (LDH) leakage was measured to assess the changes in membrane permeability. The results indicated that apigenin increased the membrane permeability and caused leakage of LDH, which was consistent with damages on membrane ultrastructure detected by AFM. Therefore, membrane toxicity, including membrane ultrastructure damages and enhanced membrane permeability, played vital roles in apigenin induced human esophageal cancer cell apoptosis. SCANNING 38:322–328, 2016. © 2015 Wiley Periodicals, Inc.